2014
DOI: 10.1179/1362171814y.0000000220
|View full text |Cite
|
Sign up to set email alerts
|

Flux modification for AC-TIG braze welding of aluminium to stainless steel

Abstract: A modified flux consisting of KAlF 4 and aluminium powder was developed for AC-TIG braze welding of aluminium to stainless steel. By employing the flux, the arc instability and wetting angle was decreased significantly, and therefore a good joint shape was obtained. The wetting and spreading behaviour as well as the action mechanism of the flux were changed. Microstructure analysis suggested that the intermetallic compound (IMC) thickness increased obviously when the addition percentage of aluminium powder in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The increased brazed joint length and the decreased wetting angle of the brazed joint affect the joint strength, as indicated in the literature [27,28]. In this study, the brazed joint length between the filler metal and steel and the wetting angle significantly increased and decreased, respectively.…”
Section: Morphology Of the Brazing Beadssupporting
confidence: 71%
“…The increased brazed joint length and the decreased wetting angle of the brazed joint affect the joint strength, as indicated in the literature [27,28]. In this study, the brazed joint length between the filler metal and steel and the wetting angle significantly increased and decreased, respectively.…”
Section: Morphology Of the Brazing Beadssupporting
confidence: 71%
“…Welding is an important fabrication technique for stainless steels, and generally, the stainless steels are considered as weldable materials. [1][2][3][4] Austenitic stainless steels represent the largest of the general groups of stainless steels due to the excellent properties such as corrosion resistance, ductility, toughness and weldability. Duplex stainless steels are compositionally formulated and thermomechanically processed to provide a two-phase microstructure exhibiting nearly equal proportions of ferrite and austenite.…”
Section: Introductionmentioning
confidence: 99%
“…Formation and growth of the interfacial IMC layer and consequent joint strengths are examined in GMA, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] gas tungsten arc (GTA) [19][20][21][22][23][24] and laser beam joining of Al alloy to galvanised steel sheets in thickness ranges of 0.8-3.0 mm. [25][26][27][28][29][30] However, these studies depict wide variations in the suggested heat input, resulting IMC layer thickness and the joint strength.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] In particular, a fair joint strength for an IMC layer thickness of around 1.6 μm is reported using coldArc, which is a specialised low heat input, pulsed current GMA process with a controlled short-circuiting metal transfer. 5 The measured values of the failure strength of aluminium to steel joints were reported to vary from 80 to 220 MPa in GMA, [4][5][6][7][9][10][11][12][13][14][15][16][17] and 120 to 180 MPa in GTA [19][20][21][22][23][24] and laser beam [25][26][27][28][29] joining techniques. These experimental studies have provided significant insights on the type of Fe-Al IMC phases and their effects on the joint strength in joining of aluminium and galvanised steel with a filler wire.…”
Section: Introductionmentioning
confidence: 99%